DIGITALISATION AND INNOVATION IN THE MANAGEMENT OF SMALL BUSINESSES - Tiurina, Alona; Skibitskiy, Oleksandr (Current Problems of Sustainable Development, 2026)
This article provides a comprehensive academic analysis of current trends in digitalisation within the management of small businesses, against the backdrop of global transformations in economic systems and sustainable development. It explores the impact of digital technologies on management flexibility and the shift from traditional hierarchical models towards networked structures. Based on the OECD’s 2025 analytical report, the Digital Maturity Index is characterised: the leaders of the global ranking are identified and Ukraine’s position is analysed in detail. An internal digital divide between micro and medium-sized companies is identified, and the level of artificial intelligence integration is assessed. Using the Network Readiness Index (NRI 2024), the asymmetry in Ukraine’s development is revealed, in particular the competitive advantage of the ‘People’ sub-index (28th place) and the vulnerability of the ‘Governance’ component (56th place). Regional differentiation in network readiness is highlighted, with a gap of 0.8 points, where Kyiv and Dnipropetrovsk region occupy the leading positions. The positive dynamics of internet access for domestic small enterprises and the expansion of cloud computing practices across sectors have been statistically proven. A hierarchy of key barriers to digitalisation has been identified, with the lack of funding and a shortage of skilled workers leading the list. The digitalisation of management is understood not merely as the technical implementation of information and communication tools, but as the systematic integration of digital solutions into processes of planning, organisation, motivation and control. The managerial benefits of digitalisation have been substantiated, consisting of reduced transaction costs, improved management efficiency and overall strategic resilience of the business in crisis conditions.